2016
DOI: 10.3109/23744235.2016.1155734
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic faecal carriage of ESBL producing enterobacteriaceae in Hungarian healthy individuals and in long-term care applicants: A shift towards CTX-M producers in the community

Abstract: 26Background: Faecal carriage of extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae 27 in healthy individuals was examined and compared to previous results obtained in such individuals a few 28 years earlier. 29Methods: Faecal samples from 779 individuals screened for employment purposes and from 225 30 applicants to long-term care (LTC) were screened between November 2013 and May 2014. 31Results: The overall rate of fecal carriage was 3.0% (30/1004). The carriage rate was significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
9
2
Order By: Relevance
“…In China, 30.1-39.3% of the total isolates collected from hospital or community acquired infections during 2003-2013 period were ESBL-positive [27]. In our study, we identified 7.94 and 12.79% of KP isolated from rodents and shrews to be ESBL-producers, the ESBL-positive rate among healthy adults was higher than that in studies conducted in Hungary [28,29]. Notably, there was no significant difference in the ESBL-positive rate among urban rodents, shrews, and healthy adults.…”
Section: Antibiotic Resistancecontrasting
confidence: 47%
“…In China, 30.1-39.3% of the total isolates collected from hospital or community acquired infections during 2003-2013 period were ESBL-positive [27]. In our study, we identified 7.94 and 12.79% of KP isolated from rodents and shrews to be ESBL-producers, the ESBL-positive rate among healthy adults was higher than that in studies conducted in Hungary [28,29]. Notably, there was no significant difference in the ESBL-positive rate among urban rodents, shrews, and healthy adults.…”
Section: Antibiotic Resistancecontrasting
confidence: 47%
“…The isolation frequencies of ESBL producers from healthy adults in Europe were usually lower than 10% [102][103][104][105][106] except for the healthy young children in Spain 107) at the end of 2016, and these values were much lower than those in Asia where the isolation frequencies are usually above 20% [108][109][110][111][112][113] . The carriage rate of ESBL producers in 2011 was reportedly 20.3% in Korea 114) .…”
Section: Esbl Prevalence Among Healthy People 4-1 Epidemiology Of Esbmentioning
confidence: 91%
“…[1] The switch from Klebsiella spp to Escherichia coli as the major ESBL-producing species is linked to the dissemination of blaCTX-M genes. [4] ESBL genes have been reported in clinical isolates, normal bacteria flora from humans and animals, food and sewage, [5] indicating the widespread distribution and presence of environmental reservoirs of the genes. [6] The carriers of ESBL-producing Enterobacteriaceae serve as a reservoir for antibiotics resistance in the community, becoming a risk to other individuals through human-to-human transmission.…”
Section: Introductionmentioning
confidence: 99%